Can a Racist Society Produce and Sustain Just and Healthy Interracial Relationships? A Few South African Case Studies - Mojapelo-Batka, E.M. (2015)
: In this study the experiences, perceptions and challenges of being in a mixed-race relationship (M-R) are explored against the backdrop of previous South African pieces of legislation meant to keep the various race groups apart. The study is located within a conceptual framework predominantly informed by a constructivist approach, including some tenets from the social constructionist approach. For the purposes of this study, six cases of mixed-race couples consisting of black and white partners only were recruited through snowball sampling. The results of the study indicate that individuals found their involvement in M-R relationships to be a positive experience, and thus resulting in a positive attitude change and a sense of personal growth. However, M-R couples and their extended families experienced cognitive dissonance which required them to discard their previously internalised racial stereotypes. To do this, strategies such as cognitive differentiation, re-categorization and de-categorization were used. This enabled the couples and their families to attempt the shift toward non-racial socially constructed categories. Most of the challenges of being in M-R relationships were experienced on both the interpersonal and the inter-group levels. The losses, disadvantages, challenges, concerns and pains experienced by M-R couples were mainly related to family and social disapproval as well as general family and social efforts aimed at discouraging race mixing